Pertanggungjawaban Pejabat Pembuat Akta Tanah Perihal Surat Pernyataan Keabsahan Pendaftaran Hak Tanggungan Elektronik - Arifatul Aininta Mardjoni; Abdul Madjid; R. Imam Rahmat Sjafi’i (University of Udayana, 2024)
After the enactment of ATR/BPN Ministerial Regulation Number 5 of 2020 concerning Electronic Integrated Mortgage Services, the regulations regarding the Statement of Validity and Veracity of Documents as a condition for registering Electronic Mortgage Rights which must be attached to the PPAT will apply. This research aims to examine in more depth the limits of PPAT's responsibility as guarantor of the Statement of Validity and Correctness of Documents, bearing in mind that the inclusion of this letter is mandatory based on article 10 paragraph 2 of the ATR/BPN Ministerial Regulation because it is part of the administrative procedure in registering the latest electronic mortgage rights. The type of research used in this research is normative legal research. The results of this research explain that the difference between Conventional Ht and Ht-el has additional provisions, where PPAT is responsible for the Letter of Accountability for the validity and correctness of the documents which are a requirement for complete registration of Mortgage Rights. This is regulated in ATR/BPN Ministerial Regulation No. 5 of 2020. However, PPAT's responsibility in terms of this statement of truth is limited to formal truth only, and is also limited to the duties of PPAT's position. However, if there is an error or negligence committed by PPAT and as long as it can be proven, then PPAT can be held administratively, civilly or criminally responsible. Setelah diberlakukannya Permen ATR/BPN Nomor 5 Tahun 2020 tentang Pelayanan Hak Tanggungan Terintregasi Secara Elektronik maka berlakulah peraturan mengenai Surat Pernyataan Keabsahan dan Kebenaran Dokumen sebagai syarat pendaftaran Hak Tanggungan Elektronik yang wajib dilampirkan PPAT. Penelitian ini bertujuan untuk mengkaji lebih dalam megenai batasan pertanggungjawaban PPAT selaku penjamin Surat Pernyataan Keabsahan dan Kebenaran Dokumen, mengingat penyertaan surat ini wajib berdasarkan pasal 10 ayat 2 Permen ATR/BPN karena merupakan bagian dari prosedur administratif dalam pendaftaran hak tanggungan eletronik yang terbaru. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian hukum normative. Hasil penelitian ini menjelaskan bahwa Perbedaan antara Ht Konvensional dan Ht-el memiliki ketentuan tambahan, di mana PPAT bertanggung jawab atas Surat Pertanggungjawaban keabsahan dan Kebenaran Dokumen yang menjadi syarat kelengkapan pendaftaran Hak Tanggungan. Hal ini diatur dalam Permen ATR/BPN No.5 Tahun 2020. Namun, pertanggungjawaban PPAT dalam hal surat pernyataan kebenaran ini sebatas kebenaran formil saja, dan juga sebatas sesuai dengan tugas jabatan PPAT. Namun jika memang terjadi kesalahan atau kelalaian yang dilakukan oleh PPAT dan selama dapat dibuktikan, maka PPAT dapat bertanggungjawab secara administratif, perdata maupun pidana.